Effect of Hypoxia on the Pathogenesis of Acinetobacter baumannii and Pseudomonas aeruginosa In Vitro and in Murine Experimental Models of Infection - Gil-Marqués, María Luisa (Infect Immun, 2018)
Hypoxia modulates bacterial virulence and the inflammation response through hypoxia-inducible factor 1α (HIF-1α). Here we study the influence of hypoxia on Acinetobacter baumannii and Pseudomonas aeruginosa infections. In vitro, hypoxia increases the bactericidal activities of epithelial cells against A. baumannii and P. aeruginosa, reducing extracellular bacterial concentrations to 50.5% ± 7.5% and 90.8% ± 13.9%, respectively, at 2 h postinfection. The same phenomenon occurs in macrophages (67.6% ± 18.2% for A. baumannii at 2 h and 50.3% ± 10.9% for P. aeruginosa at 24 h). Hypoxia decreases the adherence of A. baumannii to epithelial cells (42.87% ± 8.16% at 2 h) and macrophages (52.0% ± 18.7% at 24 h), as well as that of P. aeruginosa (24.9% ± 4.5% in epithelial cells and 65.7% ± 5.5% in macrophages at 2 h). Moreover, hypoxia decreases the invasion of epithelial cells (48.6% ± 3.8%) and macrophages (8.7% ± 6.9%) by A. baumannii at 24 h postinfection and by P. aeruginosa at 2 h postinfection (75.0% ± 16.3% and 63.4% ± 5.4%, respectively). In vivo, hypoxia diminishes bacterial loads in fluids and tissues in animal models of infection by both pathogens. In contrast, mouse survival time was shorter under hypoxia (23.92 versus 36.42 h) with A. baumannii infection. No differences in the production of cytokines or HIF-1α were found between hypoxia and normoxia in vitro or in vivo. We conclude that hypoxia increases the bactericidal activities of host cells against both pathogens and reduces the interaction of pathogens with host cells. Moreover, hypoxia accelerates the rate at which animals die despite the lower bacterial concentrations in vivo.